2023
DOI: 10.1002/anie.202306828
|View full text |Cite
|
Sign up to set email alerts
|

Triazinium Ligation: Bioorthogonal Reaction of N1‐Alkyl 1,2,4‐Triazinium Salts**

Abstract: The development of reagents that can selectively react in complex biological media is an important challenge. Here we show that N1‐alkylation of 1,2,4‐triazines yields the corresponding triazinium salts, which are three orders of magnitude more reactive in reactions with strained alkynes than the parent 1,2,4‐triazines. This powerful bioorthogonal ligation enables efficient modification of peptides and proteins. The positively charged N1‐alkyl triazinium salts exhibit favorable cell permeability, which makes t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…In our previous work, we prepared tBu-triazinium salts from 1,2,4-triazines by tert-butylation with isobutylene in the presence of triflic acid (Figure 1A). 27 However, the substrate scope of this method is inherently restricted to compounds that survive acidic conditions. Moreover, overalkylation can pose a problem for compounds containing additional reactive nucleophilic sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we prepared tBu-triazinium salts from 1,2,4-triazines by tert-butylation with isobutylene in the presence of triflic acid (Figure 1A). 27 However, the substrate scope of this method is inherently restricted to compounds that survive acidic conditions. Moreover, overalkylation can pose a problem for compounds containing additional reactive nucleophilic sites.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we established that a C 5 -phenyl-substituted triazinium, with diethylaminocoumarin attached through a phenylmethylene amino linker at position C 3 , exhibits a 6.5-fold increase in fluorescence upon reaction with endo-BCN. 27 We discovered that substituting the phenyl group at C 5 with an electrondonating 4-methoxyphenyl yielded triazinium derivative Trz + Coum6, which exhibited a notable enhancement in fluorescence upon reaction with endo-BCN in phosphatebuffered saline (PBS). On the basis of these findings, we designed a second generation of fluorogenic Trz + Coum probes containing the dye attached to the triazinium core through the conjugated phenyl ring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Very recently Vrabel and co-workers introduced N1-alkyl-1,2,4-triazinium salts as an efficient diene system in reaction with BCN. 7 Metal coordination is another way to facilitate the IEDDA reaction, and it was shown that both tetrazines and triazines react much faster in IEDDA reactions if directly coordinated to a metal ions. For example, Lo and co-workers were first to demonstrate this effect in tetrazine Ir(III) complexes.…”
Section: Introductionmentioning
confidence: 99%